Prevention of Malaria Resurgence in Greece through the Association of Mass Drug Administration (MDA) to Immigrants from Malaria-Endemic Regions and Standard Control Measures. - Maria Tseroni; Agoritsa Baka; Christina Kapizioni; Georges Snounou; Sotirios Tsiodras; Maria Charvalakou; Maria Georgitsou; Maria Panoutsakou; Ioanna Psinaki; Maria Tsoromokou; George Karakitsos; Danai Pervanidou; et al. (Public Library of Science (PLoS), 2015)
Greece was declared malaria-free in 1974 after a long antimalarial fight. In 2011-2012, an outbreak of P. vivax malaria was reported in Evrotas, an agricultural area in Southern Greece, where a large number of immigrants from endemic countries live and work. A total of 46 locally acquired and 38 imported malaria cases were detected. Despite a significant decrease of the number of malaria cases in 2012, a mass drug administration (MDA) program was considered as an additional measure to prevent reestablishment of the disease in the area. During 2013 and 2014, a combination of 3-day chloroquine and 14-day primaquine treatment was administered under direct observation to immigrants living in the epicenter of the 2011 outbreak in Evrotas. Adverse events were managed and recorded on a daily basis. The control measures implemented since 2011 continued during the period of 2013-2014 as a part of a national integrated malaria control program that included active case detection (ACD), vector control measures and community education. The MDA program was started prior to the transmission periods (from May to December). One thousand ninety four (1094) immigrants successfully completed the treatment, corresponding to 87.3% coverage of the target population. A total of 688 adverse events were recorded in 397 (36.2%, 95% C.I.: 33.4-39.1) persons, the vast majority minor, predominantly dizziness and headache for chloroquine (284 events) and abdominal pain (85 events) for primaquine. A single case of primaquine-induced hemolysis was recorded in a person whose initial G6PD test proved incorrect. No malaria cases were recorded in Evrotas, Laconia, in 2013 and 2014, though three locally acquired malaria cases were recorded in other regions of Greece in 2013. Preventive antimalarial MDA to a high-risk population in a low transmission setting appears to have synergized with the usual antimalarial activities to achieve malaria elimination. This study suggests that judicious use of MDA can be a useful addition to the antimalarial armamentarium in areas threatened with the reintroduction of the disease.